PENGARUH KINERJA APARATUR PEMERINTAH DAERAH, PENGELOLAAN KEUANGAN DAERAH, SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) DAN KOMITMEN ORGANISASI TERHADAP PENERAPAN GOOD GOVERNANCE (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Rokan Hulu) - Weni Nirmala Sari; Vince Ratnawati; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine (1)The effect of the local government officials performance on the good governance implementation (2) The effect of the local financial management on the good governance implementation (3) The effect of the government's internal control system on the good governance implementation and (4) The effect of the organization commitment on the good governance implementation. The sample on this study are all of SKPD in Rokan Hulu regency. Hipotesist in this study are tested using Statistical Product and Service Solution (SPSS) program ver. 20.0. This study used a primer datas obtained through questionnaires given to chief officer, chief financial officer, chief planning and programming officer, and chief public and personnel officer. From 100 sets questionnaires distributed, 93 sets questionnaires returned and due to missing data/incomplete answer so only 88 sets questionnaires were analyzed. The result of this study found that (1) the local government officials performance positively effect the good governance implementation, (2) financial management positively effect the good governance implementation, (3) the government's internal control system positively effect the good governance implementation and (4) organization commitment positively effect the good governance implementation.Keyword: Governance, Performance, Financial, System, and Organization.